Parent concerns regarding paediatric obesity in community‐based programmes serving children with developmental disabilities. (27th August 2020) - Natale, Ruby; Weerakoon, Sitara; Woody, Malaika T.; Kolomeyer, Ellen; Pena, Kristyna; Schladant, Michelle; Bulotsky‐Shearer, Rebecca J.; Messiah, Sarah E.
Abstract: Background: Previous studies show a higher prevalence of obesity among preschool‐age children with developmental disabilities (DDs) versus children who are typically developing (TD). Little is known about parent concerns about obesity in young children with DD. The purpose of this study was to examine concerns regarding paediatric obesity among parents who had a preschool‐age child with DD compared with parents with a child who is TD. Methods: A cross‐sectional analysis occurred at baseline entry into one of three community‐based programmes. Parents of a child with DD ( n = 815) or TD ( n = 563) were asked obesity‐related questions about their child and in general. Multinomial and logistic regression unadjusted and adjusted models were run to generate the odds of obesity concerns based on disability status. Results: The average child age was 38 months. Parent concerns about paediatric obesity differed by disability status. Unadjusted odds of parents 'doing anything to control their child's weight' was 38% lower among parents of a child with DD versus TD (OR: 0.62, 95% CI: 0.48, 0.82). The adjusted odds of perceiving that their child was underweight was 83% higher among parents of a child with DD compared with parents of a child who is TD (aOR: 1.83, 95% CI: 1.27, 2.64). Parents of a child with DD were 179% more likely to believe that childhood obesity is a public health problem (aOR: 2.79, 95% CI: 1.88, 3.96). The models were adjusted for age, sex and race/ethnicity. Conclusions: Findings indicate that parents of preschool‐age children with DD are more likely to acknowledge that obesity is a public health concern. Because some parents of children with DD are concerned about their child's weight, families of preschool‐age children with DD may be receptive to the delivery of healthy weight strategies in community‐based programs.